Human immunodeficiency virus‐infected young people in Australia: data from the Australian HIV Observational Database3. Issue 12 (5th December 2018) - Hughes, Carly; Puhr, Rainer; Ojaimi, Samar; Petoumenos, Kathy; Bartlett, Adam W.; Templeton, David J.; O'Connor, Catherine C.; Gunathilake, Manoji; Woolley, Ian
Abstract: Background: Individuals aged 13–24 years undergo vast physical, cognitive, social and psychological changes. Australian data regarding clinical outcomes of those diagnosed with HIV in this age are sparse. Aim: We aimed to describe demographic factors, virologic and clinical outcomes of individuals aged 13–24 years diagnosed with human immunodeficiency virus (HIV). Methods: Patients diagnosed with HIV after 1997 in the Australian HIV Observational Database were divided into young adults, diagnosed at age <25 years ( n = 223), and older adults ( n = 1957). Demographic and clinical factors were compared between groups. Results: Young adults had a median age at diagnosis of 22 years (inter quartile range (IQR) 20–24) and median age at treatment initiation of 24 years (IQR 22–26). They were more likely to be female than the older cohort (21.1 vs 10.8%; P < 0.001). Men who have sex with men was the most common exposure category in both groups. CD4 count at diagnosis was significantly higher in younger than older adults (median 460 vs 400 cells/mm 3, P = 0.006), whereas HIV viral load at diagnosis was lower (35 400 vs 61 659 copies/mL, P = 0.011). The rate of loss to follow up (LTFU) was higher in young adults (8.0 vs 4.3 per 100PY, P < 0.001). Young adults were more likely to have a treatment interruption compared to older adults (5.3 vs 4.0 per 100PY, P = 0.039). Rates of treatment switch, time to treatment change, and CD4 and viral load responses to treatment were similar between groups. Conclusions: Young adults were diagnosed with HIV at higher CD4 counts and lower viral loads than their older counterparts. LTFU and treatment interruption were more common highlighting the need for extra efforts directed towards retention in care and education regarding the risks of treatment interruptions.